2015
DOI: 10.1089/jmf.2013.0055
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of the Methanolic Extract of Turnera diffusa Willd on Breast Cancer Cells

Abstract: Turnera diffusa Willd, commonly known as Damiana, is employed in traditional medicine as a stimulant, aphrodisiac, and diuretic. Its leaves and stems are used for flavoring and infusion. Damiana is considered to be safe for medicinal use by the FDA. Pharmacological studies have established the hypoglycemic, antiaromatase, prosexual, estrogenic, antibacterial, and antioxidant activity of T. diffusa. The aim of the present study was to evaluate the possible cytotoxic effect of extracts and organic fractions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Regarding the cytotoxic effect of apigenin on HeLa cells, our study showed lower IC 50 values than others, with reported IC 50 values of 40 μ M at 30 h [ 39 ] and 37 μ M at 24 h [ 41 ]. We have knowledge of only one study that investigated the cytotoxic activity of apigenin on SiHa and C33A cells [ 64 ] that used the same concentrations and times used here (0–100 μ M at 72 h). The results from that study are similar to ours: apigenin was cytotoxic for both SiHa and C33A cells with IC 50 values of 50.14 μ M and 45.10 μ M, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the cytotoxic effect of apigenin on HeLa cells, our study showed lower IC 50 values than others, with reported IC 50 values of 40 μ M at 30 h [ 39 ] and 37 μ M at 24 h [ 41 ]. We have knowledge of only one study that investigated the cytotoxic activity of apigenin on SiHa and C33A cells [ 64 ] that used the same concentrations and times used here (0–100 μ M at 72 h). The results from that study are similar to ours: apigenin was cytotoxic for both SiHa and C33A cells with IC 50 values of 50.14 μ M and 45.10 μ M, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The other chemical classes evaluated had moderate presence in the evaluated extracts. Studies already reported in the literature show that arbutin and apigenin flavonoids are the main chemical constituents of Turnera diffusa with cytotoxic activity, present in methanolextract (AVELINO-FLORES et al, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…Its traditional use dates back to ancient Mayan and Mexican indigenous groups that prepared medicinal beverage for giddiness treatment and as an aphrodisiac [24,25]. Currently, several damiana products have been commercially available for their use as aphrodisiac, diuretic, and cancer and diabetes treatments [26,27]. T. difussa extracts contain more than 47 organic compounds comprised of flavonoids, terpenoids, saccharides, phenolics, and cyanogenic derivatives [28].…”
Section: Introductionmentioning
confidence: 99%